The Impact of Telemedicine on Patient Outcomes During the COVID-19 Pandemic: A Systematic Review and Meta-Analysis - Ningsih, Kori Puspita; Anshoriyah, Sofiyatul; Nurcahyanti, Khusnul Khotimah Arum; Handayani, Titi Purwitasari; Ningrum, Dedah (PT Inovasi Pratama Internasional, 2025)
The ongoing global pandemic has precipitated the rapid adoption of telemedicine as an alternative means of delivering healthcare, particularly with a view to reducing direct contact between patients and medical personnel. The objective of this study is to examine the influence of telemedicine on patient health outcomes during the ongoing pandemic through a comprehensive review and meta-analysis of pertinent literature. A qualitative research methodology was employed to analyse 20 articles selected based on pre-established inclusion and exclusion criteria. The findings indicate that telemedicine has a favourable impact on enhancing healthcare accessibility, time efficiency and cost reduction, despite challenges pertaining to technological constraints and patient digital proficiency. This research offers valuable insights for policymakers in optimising the future implementation of telemedicine.